Research on Motor Vehicle Travel Trip Test for Low Carbon Transportation in ITS - Wang, Haiwei; Wen, Huiying; Tian, Liyou; You, Feng; Kui, Hailin; Georgiou, George (Recent Patents on Computer Science, 2014)
Today more and more people have concerned about how to reduce the energy consumption of vehicles on road in urban city. This paper uses the petrol car as research object, researching the energy saving of vehicles in conditions of real urban transportation. The best travel route of the energy saving is found by comparing different travel routes, and it is finally proved that there exists a travel route that may not be the shortest one but is the one which has the least fuel consumption. Firstly, two experimental lines are selected which have the same origin and destination but have different travel routes. By using the geographic information of Google Earth, we collected the information of latitude and longitude based on the manually labeled, and combined MATLAB to generate the road map of city with intersection identifies. We chose two trial routes, and used separately fuel consumption instrument to collect fuel consumption data of vehicles by doing vehicle test on two different paths of the trial route. Secondly, test database is built and relative data is manipulated. According to the changes of city's traffic flow in one day, test time is divided into four different periods: morning peak period, morning off-peak period, evening off-peak period and evening peak period, the data of every period is divided into leaving trip and returning trip, and database is built by MATLAB. The vehicle fuel consumption is contrastively analyzed from different angles, such as period and direction. According to the experiment data, the average speed and percentage of idle time were calculated, and fuel consumption model per 100 kilometers was established based on these two parameters. Results of calculation with model are in agreement with the fuel consumption of test to a certain extent, therefore, it is also proved with patents that the fuel consumption model has high reliability.
Keywords: traffic parameters